Diffusion welding of nickel-based superalloys - Rezaei, Hossein (Diffusion Fundamentals, 2011)
Ni based superalloys can be welded by diffusion bonding. Temperature, diffusion coefficient, activation energy and Boltzmann constant influence the quality of diffusion bonding, so obtaining the best condition for welding is considered. Showing the suitable condition for diffusion welding of nickel-based superalloys is the aim of this paper.